Answer:
[tex]y = -3x[/tex]
Step-by-step explanation:
Given
The attached graph
Required
Determine the graph equation
To do this, we pick any 3 corresponding points of x and y
[tex](x_1,y_1) = (0,0)[/tex]
[tex](x_2,y_2) = (2,-6)[/tex]
[tex](x_3,y_3) = (-4,12)[/tex]
The equation can then be solved using linear interpolation as follows:
[tex]\frac{y-y_3}{x-x_3} = \frac{y_2 - y_1}{x_2-x_1}[/tex]
This gives:
[tex]\frac{y-12}{x-(-4)} = \frac{-6 -0}{2-0}[/tex]
[tex]\frac{y-12}{x+4} = \frac{-6 -0}{2-0}[/tex]
[tex]\frac{y-12}{x+4} = \frac{-6}{2}[/tex]
[tex]\frac{y-12}{x+4} = -3[/tex]
Multiply both sides by x + 4
[tex](x + 4) * \frac{y-12}{x+4} = -3 * (x + 4)[/tex]
[tex]y - 12 = -3 *(x + 4)[/tex]
Open bracket
[tex]y - 12 = -3x -12[/tex]
Add 12 to both sides
[tex]y - 12+12 = -3x -12+12[/tex]
[tex]y = -3x[/tex]